Molecular and Cellular Mechanisms of Lipid Droplet Breakdown in the Liver of Chinese Soft-Shelled Turtle (Pelodiscus sinensis) - Huang, Yufei; Yang, Sheng; Bai, Xuebing; Shi, Yonghong; Chen, Qiusheng (Frontiers in Marine Science, 2021)
The Chinese soft-shelled turtle (Pelodiscus sinensis) is among the most primitive amphibians and reptiles in nature. On account of its environmental suitability and unique hibernation habit, the peculiar physiological phenomenon in P. sinensis attracted the attention of researchers in the field of marine science. The present study aimed to investigate the molecular mechanisms underlying the periodic variation of lipid droplet (LD) in the liver of P. sinensis. Histological results indicated that accumulated LD in the liver of P. sinensis during non-hibernation was gradually consumed during hibernation. RNA-Seq results revealed that genes responsible for carbohydrate catabolism were down-regulated during hibernation, while genes involved in lipid oxidation were up-regulated. These results suggest that energy metabolism in the liver of P. sinensis changes during hibernation, i.e., the energy generation mode shifted from carbohydrate catabolism to lipid oxidation. Further analysis of RNA-Seq results indicated that both lipolysis and autophagy could promote the degradation of hepatic LD during hibernation. To further determine the relationship between lipolysis and autophagy in the process of LD breakdown, we applied the inhibitors of lipolysis and autophagy (diethylumbelliferyl phosphate and 3-Methyladenine) in cultured primary hepatocytes of P. sinensis. The results indicated that lipolysis is the main way for LD degradation in the hepatocyte of P. sinensis. These data provide clear evidence about the seasonal changes in hepatocytes, corresponding with the different energy generation mode in the liver of P. sinensis.